Life course linkages between enriching early-life activities and later life cognition: Evidence from the Wisconsin Longitudinal Study. (February 2022) - Greenfield, Emily A.; Reynolds, Addam; Moorman, Sara M.
Abstract: Prior research suggests that participation in enriching early-life activities (EELAs) has long-term benefits for cognitive health and aging. This study aims to examine the life course processes underlying these associations by drawing on theoretical models from life course epidemiology. Specifically, we tested sensitive-period effects, social pathways, and selection effects as potential explanations for linkages between greater participation in EELAs and better later life cognition. We drew on data from the Wisconsin Longitudinal Study (WLS), which is among the longest-running cohort studies in the U.S. that has followed graduates (all identified as non-Hispanic White) from Wisconsin high schools since 1957. We used prospective measures of key variables, including information from high school yearbooks, with assessments of cognitive performance at ages 65 and 72. Results from multilevel modeling indicated that greater participation in cognitively oriented extracurricular activities (but not physically nor socially oriented activities) was associated with both better language/executive functioning and memory at age 65. Although the size of these associations was reduced when accounting for other cognitive resources in adolescence (childhood socioeconomic status and adolescent cognitive ability) and in midlife (adult socioeconomic status and formal group participation), there remained small, yet statistically robust, associations. We did not find robust associations between greater EELA engagement and slower rates of decline in cognition between ages 65 and 72, nor did we find evidence of gender differences. Results suggest that for this cohort of older adults, EELA participation is part of life course "protective chains, " whereby exposures to assets at one point in the life course increase the likelihood of subsequent exposures, each sequentially and in their own right, toward better later life cognition. We discuss how results support the importance of policies and practices to promote healthy cognitive development among youth for the long-term cognitive health of a rapidly aging U.S. population. Highlights: Enriching activities in youth are associated with cognitive benefits in later life. Sensitive periods, social pathways, and selection each account for the associations. There were no differences in the long-term protective effects for men versus women.